Operational evaluation of thermal barrier coated diesel engine fueled with biodiesel/diesel blend by using MCDM method base on engine performance, emission and combustion characteristics - SAYIN, CENK (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
In this study, engine operating conditions which given the best result in terms of performance, exhaust emission and combustion characteristics in a thermal barrier coated (TBC) diesel engine, which was covered with ceramic on combustion chamber elements, were determined by multi-criteria decision-making (MCDM) method. It was also included in the optimization of the data obtained from the uncoated (standard) engine (STD) in order to better evaluate the TBC engine. In the experimental study, diesel, pure biodiesel derived from cotton oil frying waste and biodiesel/diesel blend fuels (5, 20 and 50% by volume) were used as fuel. In optimization, operational competitiveness rating (OCRA) was preferred as a MCDM. The experimental data, which included a total of six hundred data, in TBC and STD engines fueled biodiesel and its blends were used in optimization. According to the optimization result, the best results in terms of engine performance, exhaust emission and combustion characteristics were generally obtained from the TBC engine. According to the optimization sequence, the ranking obtained from the TBC engine were observed to be ahead of the STD engine at all engine speeds. It was also found that the best results were concentrated at engine speeds of 1800 rpm and 2100 rpm. The best result was achieved by using B20 (20% biodiesel + 80% diesel) in TBC engine at 1800 rpm. The performance, emission and combustion characteristics obtained under these optimum operating parameters (OOP) were also compared with those of the STD engine fueled with B0 and B100. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Diesel engine; Thermal barrier coating; Multi-criteria decision-making; OCRA; Optimum operating parameters; NOISE; OIL; VIBRATIONS